Pelatihan Pengembangan Model Pembelajaran Menulis Teks Deskripsi dengan Picture Word Inductive Model - Jumariati Jumariati; Eka Puteri Elyani; Rizky Amelia; Khairin Utomo; Mardatilah Nadya Ramadanty; Rika Rianti (WARTA LPM, 2021)
Writing skills are rarely taught since many teachers encounter issues such as students' poor command of English vocabulary, inability to write in the correct English format, insufficient time allotted to aid each student, and a lack of teacher expertise regarding teaching strategies. For students, appropriate writing skills are required. Activities such as training for English teachers on approaches for teaching suitable and engaging writing skills to students are required. The Picture Word Inductive Model will be taught as a tool for practicing writing descriptive text abilities. This activity employs a participatory technique based on Kurt Lewin's theory, which stresses the target participants' active participation throughout the training process, from participating in training activities to completing training assignments. A total of 15 teachers from various agencies in Kabupaten Banjar participated in this community service project. Starting with the explanation, questions and answers session, small group discussions, reflection, and evaluation, the exercise went off without a hitch. The Picture Word Inductive Model is a learning paradigm that they have just acquired and will employ in teaching writing. Because there were steps of categorizing and refining it into phrases and paragraphs, participants concluded that utilizing this model would be better than using visual media. As a result, they can assist students with their writing. In a nutshell, English teachers in Kabupaten Banjar have a good conceptual understanding of how to teach descriptive text writing skills. Finally, the participants were able to create a learning plan for writing descriptive text skills using Picture Word Inductive Model.